Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Câu 2.
=>x +4<11
=>x=0;1;2;3;4;5;6
=>x +4>9
=>x=6;7;8;9;...
=> x=6
\(\left(1+x\right)+\left(2+x\right)+\left(3+x\right)+\)\(\left(4+x\right)+\left(5+x\right)=10\times5\)
\(\left(1+2+3+4+5\right)+\left(x+x+x+x+x\right)=50\)
\(15+5x=50\)
\(5x=35\)
\(x=7\)
Vậy \(x=7\)
\(\left(1+x\right)+\left(2+x\right)+\left(3+x\right)+\left(4+x\right)+\left(5+x\right)=10\times5\)
\(\Rightarrow1+x+2+x+3+x+4+x+5+x=50\)
\(\Rightarrow\left(1+2+3+4+5\right)+\left(x+x+x+x+x\right)=50\)
\(\Rightarrow15+5x=50\)
\(\Rightarrow5x=50-15\)
\(\Rightarrow5x=35\)
\(\Rightarrow x=35:5\)
\(\Rightarrow x=7\).
x/18 < 11/72
4x / 72 < 11 / 72
=> 4x < 11
=> 4x thuộc B ( 4 )
B ( 4 ) thuộc { 0 ; 4 ; 8 ]
Th1 : 4 x = 0
x = 0 : 4
x = 0
Th2 : 4x =4
x = 4 : 4
x = 1
Th3 : 4x = 8
x= 8 : 4
x = 2
Vậy x thuộc { 0 ; 1 ; 2 }
\(\frac{3}{4}+x=\frac{5}{7}\cdot\frac{14}{5}\)
= \(\frac{3}{4}+x=6\)
\(x=6-\frac{3}{4}\)
\(x=\frac{21}{4}\)
a) \(\left(x+\frac{3}{4}\right):5=\frac{5}{6}\)
\(x+\frac{3}{4}=\frac{5}{6}\text{x}5\)
\(x+\frac{3}{4}=\frac{25}{6}\)
\(x=\frac{25}{6}-\frac{3}{4}\)
\(x=\frac{41}{12}\)
b) \(\left(\frac{4}{3}+x\right)\text{x}\frac{1}{11}=\frac{7}{11}\)
\(\frac{4}{3}+x=\frac{7}{11}:\frac{1}{11}\)
\(\frac{4}{3}+x=7\)
\(x=7-\frac{4}{3}\)
\(x=\frac{17}{3}\)
a) \(x+\frac{3}{4}\div5=\frac{5}{6}\)
\(x+\frac{3}{4}=\frac{5}{6}\times5\)
\(x+\frac{3}{4}=\frac{25}{6}\)
\(x=\frac{25}{6}-\frac{3}{4}\)
\(x=\frac{41}{21}\)
b) \(\left(\frac{4}{3}+x\right)\times\frac{1}{11}=\frac{7}{11}\)
\(\frac{4}{3}+x=\frac{7}{11}\div\frac{1}{11}\)
\(\frac{4}{3}+x=7\)
\(x=7-\frac{4}{3}\)
\(x=\frac{17}{3}\)
b) \(x:\frac{4}{5}=\frac{5}{2}\)
=> \(x=\frac{5}{2}\cdot\frac{4}{5}=2\)
c) \(\frac{2}{9}:x=\frac{2}{3}\)
=> \(x=\frac{2}{9}:\frac{2}{3}=\frac{2}{9}\cdot\frac{3}{2}=\frac{1}{3}\)
\(x+\frac{15}{7}=\frac{9}{2}\)
\(x=\frac{9}{2}-\frac{15}{7}=\frac{33}{14}\)
\(x-\frac{3}{4}=\frac{7}{2}\)
\(x=\frac{7}{2}+\frac{3}{4}=\frac{17}{4}\)
\(x.\frac{7}{8}=\frac{12}{5}\)
\(x=\frac{12}{5}:\frac{7}{8}=\frac{96}{35}\)
\(\frac{5}{6}:x=\frac{4}{3}\)
\(x=\frac{5}{6}:\frac{4}{3}=\frac{5}{8}\)
- a) x=9/2-15/7=33/14
- b) x=7/2+3/4=17/4
- c) x=12/5:7/8=61/35
- d) x=5/6:4/3=5/8
- k nha
a,
x.2/7.3/4=5/21
x.3/14=5/21
x=5/21:3/14
x=10/9
b,
x.1/2=1/3
x=1/3:1/2
x=2/3
c,
x:4/5=25/8:5/4
x:4/5=5/2
x=5/2.4/5=2
A, x= 5/25 : 3/4 : 2/7 = 14/15
B, x=1/3 : 1/2 = 2/3
C, x=(25/8 : 5/4)x4/5 = 5/2 x 4/5 = 2
x × 4, 5= 72
x = 72 : 4,5
x = 16